Pendampingan Legalitas Usaha Melalui Penerbitan NIB dan HKI pada UMKM Golden Kriuq di Kalideres - Hana Bella Sartika; Muhammad Arvin Aldrich Romero; Fitrisia Gita; Budi Setiawan (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Business legality is an urgent need for MSMEs, particularly in the food sector, which faces strict regulations and high risks to food safety. However, many MSMEs still lack a Business Identification Number (NIB) or Intellectual Property Rights (IPR) protection due to low digital literacy and a lack of understanding of licensing procedures. This situation emphasizes the urgency of mentoring so that MSMEs can operate legally and be legally protected. This Community Service Program (PKM) aims to assist the Golden Kriuq MSME in obtaining an NIB and increase business owners' understanding of the importance of IPR, branding, and digital marketing. The implementation method uses a qualitative approach through observation, interviews, education, documentation, and direct mentoring. Activities carried out include NIB registration through the OSS Indonesia application, logo, banner, and menu design, business Instagram account creation, location determination on Google Maps, and education on the stages of brand registration through the DJKI system. The results show that Golden Kriuq successfully obtained an NIB, has a more consistent visual identity, and has a more professional digital presence. The program's impact is evident in increased awareness of legality, digital administration readiness, and businesses' ability to compete more professionally and sustainably.